SOMATIC EMBRYOGENESIS IN MAIZE: BACKGROUND AND EFFICIENCY - LUCENA, ANA LUISA MONEZI; DE OLIVEIRA ELOI, IVONE BATISTA; MANGOLIN, CLAUDETE APARECIDA; DA SILVA MACHADO, MARIA DE FÁTIMA PIRES (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
The selection of efficient protocols to promote somatic embryogenesis and plant regeneration of maize (Zea mays L.), is a target that should contribute to the improvement of maize in Brazil. This process should encourage the transfer of genes and the development of genetically modified varieties. In the present review, protocols have been organized and developed for embryogenic callus induction and plant regeneration in order to evaluate the efficiency of the protocols that were used. One or more promising protocols for future investments was selected with genotypes of interest for genetic improvement. The investigations with different maize genotypes are concentrated in just over two decades (1989-2012), when only 17 studies were published and 179 genotypes were investigated, of which 77% formed embryogenic callus and only 43.5% regenerated plants in the absence or presence of amino acids and/or in different concentration of cytokinins and auxins. The N6 medium was the most used for callus induction (89.47% of investigations). The addition of L-proline, hydrolyzed casein, along with AgNO3 was detected in 84, 56, and 60% of the experiments, respectively. N6 medium containing 2.0 mg L-1 2.4-D has been used to analyze 46% of the genotypes. Through this process somatic embryogenesis has been induced in 87.9% of these cases. It has been three decades since the release of the first corn regenerant (1975), the competence for somatic embryogenesis and plant regeneration has been linked to being more dependent on genotype than on added supplements to the culture medium.